VD_FINDINFO Décision / 2015 / 861 vom 24. November 2015 - VD Tribunal cantonal (2015)
DÉTENTION PROVISOIRE, RISQUE DE COLLUSION, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH), 222 CPP (CH), 393 al. 1 let. c CPP (CH)